Bone health in autosomal dominant polycystic kidney disease (ADPKD) patients after kidney transplantation - Dalia Zubidat; Christian Hanna; Amarjyot K. Randhawa; Byron H. Smith; Maroun Chedid; Daniel-Hasan N. Kaidbay; Luca Nardelli; Yaman G. Mkhaimer; Reem M. Neal; Charles D. Madsen; Sarah R. Senum; Adriana V. Gregory; et al. (Bone Reports, 2023)
ADPKD is caused by pathogenic variants in PKD1 or PKD2, encoding polycystin-1 and -2 proteins. Polycystins are expressed in osteoblasts and chondrocytes in animal models, and loss of function is associated with low bone mineral density (BMD) and volume. However, it is unclear whether these variants impact bone strength in ADPKD patients. Here, we examined BMD in ADPKD after kidney transplantation (KTx). This retrospective observational study retrieved data from adult patients who received a KTx over the past 15 years. Patients with available dual-energy X-ray absorptiometry (DXA) of the hip and/or lumbar spine (LS) post-transplant were included. ADPKD patients (n = 340) were matched 1:1 by age (±2 years) at KTx and sex with non-diabetic non-ADPKD patients (n = 340). Patients with ADPKD had slightly higher BMD and T-scores at the right total hip (TH) as compared to non-ADPKD patients [BMD: 0.951 vs. 0.897, p < 0.001; T-score: −0.62 vs. -0.99, p < 0.001] and at left TH [BMD: 0.960 vs. 0.893, p < 0.001; T-score: −0.60 vs. -1.08, p < 0.001], respectively. Similar results were found at the right femoral neck (FN) between ADPKD and non-ADPKD [BMD: 0.887 vs. 0.848, p = 0.001; T-score: −1.20 vs. -1.41, p = 0.01] and at left FN [BMD: 0.885 vs. 0.840, p < 0.001; T-score: −1.16 vs. -1.46, p = 0.001]. At the LS level, ADPKD had a similar BMD and lower T-score compared to non-ADPKD [BMD: 1.120 vs. 1.126, p = 0.93; T-score: −0.66 vs. -0.23, p = 0.008]. After adjusting for preemptive KTx, ADPKD patients continued to have higher BMD T-scores in TH and FN. Our findings indicate that BMD by DXA is higher in patients with ADPKD compared to non-ADPKD patients after transplantation in sites where cortical but not trabecular bone is predominant. The clinical benefit of the preserved cortical bone BMD in patients with ADPKD needs to be explored in future studies.